«For a dignified work» - Emergency and representations of a movement of working children and adolescents in Bolivia - Rutigliano, Alexandre (2019)
Since the first organisations of working children and adolescents (NNAT) emerged in the 1980’s in Bolivia, they have been leading ongoing actions in collaboration with and against the State, including the writing of the New Constitution in 2008-9 and of the New Child and Adolescents Code in 2013-14. As a social movement, they have been fighting for their rights to work, to have special legal protections for being working children and to be involved in the design of laws and policies that affect them. As part of a broader ethnographic investigation, this article focuses on the history of the the representations of childhood and work that are still today dominant in most international organisations, and on how some bolivian NNAT confront them and define more contextualised and inclusive rights. Overall, this work shows that there is no universal way of being a child, and that children and adolescents must be considered as actors in the social and political spheres.